Experimental investigation on the thermal and moisture mapping of cricket helmets using microsensor technology. (January 2020) - Guan, Z.W.; Dullah, A.R.; Yuan, R.; Chen, Y.; Wang, Q.Y.
Highlights: Combined temperature and moisture microsensors are embedded in two types of helmets. In-helmet thermal and moisture mappings have been obtained for the first time. Human perceptions on warmth, moisture and thermal comfort have been recorded. Comfort index is linked to the measured in-helmet temperature and relative humidity. Abstract: Based on microsensor technology, a novel test rig was developed for the first time to measure real-time multi-point temperatures and relative humidities inside a cricket helmet worn by a human subject for obtaining the corresponding thermal and moisture mapping. Two types of helmets with and without ventilation openings were investigated to visualise the hot and wet spots clearly inside the helmet. The results show the clear influence of ventilation openings on effective reduction of the temperature as well as the relative humidity inside the helmet. Also, the subjective data were linked to the digital temperature and relative humidity measurements for possible assisting design of helmet with improved thermal comfort. The technology developed is a useful measurement approach to other head gears such as safety, fire fighter and motorcycle helmets, and further to study microclimate environments in close contact with human body.